Prevalence of new variants of Fusarium udum in India - TIWARI, SHASHI; DHAR*, VISHWA (Indian Phytopathology, 2011)
Fusarium udum causes wilt of pigeonpea, which is the most important disease in India. The pathogen shows arange of cultural, morphological and pathogenic variability. Three culturally, morphologically, and pathogenically distinctisolates (F3, F8 and F17) selected from 51 isolates of the pathogen collected from Kanpur and Kanpur Dehat district, were studiedÂ for reactions on 15 differential genotypes of pigeonpea during 2003-2004. The three isolates exhibited differential response to10 genotypes warranting them to be distinguished as three different variants of F. udum, which have been designated asvariant 2, 4 and 5. Earlier reports reveal prevalence of variant 1, 2 and 3 (strain 1, 2 and 3) in different parts of the country. Thusas on now, prevalence of 5 distinct pathogenic variants (variants 1, 2, 3, 4 and 5) in F. udum can be inferred in the country.